A Monoclonal IgM Antibody With Specificity To Heat Shock Protein GRP78/BIP Shows Anti- Myeloma Activity In Vitro and In Vivo, Synergy In Combination With Lenalidomide and Safety In a Pilot Phase I Study - Rasche, Leo; Braendlein, Stephanie; Duell, Johannes; Knop, Stefan; Dubljevic, Valentina; Rosenwald, Andreas; Einsele, Hermann; Topp, Max S. (Blood, 2013)
Monoclonal antibodies have entered the therapy of multiple myeloma (MM) and are currently being evaluated in phase I-III trials. PAT-SM6 is a fully human IgM antibody that specifically binds to a cancer-specific cell surface variant of the chaperone molecule glucose regulated protein 78 (GRP78). Finding a GRP78 cancer-specific form on the surface of cancer cells, but not normal cells in vivo, presents an opportunity for cancer-specific targeting. This antibody is able to specifically target primary myeloma cells without showing cross-reactivity to healthy tissues (including plasma cells from healthy donors). Moreover, antibody treatment in vitro led to apoptosis in primary myeloma cells (Rasche L; PLOS One 2013). In vitro,PAT-SM6 was combined with Lenalidomide and/or Bortezomib and Dexamethasone in double and triple combinations on myeloma cell lines. Synergistic and additive cytotoxic effects were analyzed using the Chou-Talalay method. All double and triple combinations showed synergistic effect with a combination index (CI) <1. In all double combinations, low doses of agents appear more effective than high doses. In triple, PAT-SM6 + Dexamethasone + Lenalidomide seem to be the most efficient combination (CI from 0.005 to 0.011). In vitro data is further supported by positive in vivodata using PAT-SM6 in a 5T33 multiple myeloma mouse model. Upon injection of 5T33 cells mice developed multiple myeloma disease with clinical, biological and genetic characteristics similar to those of the human disease. A total of 6 doses PAT-SM6 were given i.p. followed by the collection of serum and bone marrow samples. Doses >10mg/kg resulted in a significant reduction of plasma cells in the bone marrow (up to 54%) and a reduction of blood levels (up to 48%) of M protein. No cytotoxicity was observed. Based on these results we performed a Phase I clinical trial to examine the tolerability and safety of the PAT-SM6 antibody in patients with relapsed / refractory multiple myeloma. A pilot Phase I dose-escalating study was initiated (NCT01727778). Relapsed myeloma patients according to IMWG criteria were treated in different dose cohorts (0.3, 1,3 and 6mg/kg/dose) with at least four doses of PAT-SM6 as single agent in a two week cycle. A serological staging was performed on day 36. At the date of the abstract submission 9/12 subjects were treated. PAT-SM6 therapy was very well tolerated. No dose limiting toxicity (DLT), no related SAE and no related adverse events greater than grade 3 were observed. Mild leucopenia seemed to be a specific side effect. At date of submission 8 patients are evaluable for response. Two out of 8 patients showed stable disease according to IMWG criteria. In summary, PAT-SM6 provides a very promising approach for the immune therapy of patients with relapsed and refractory multiple myeloma. Braendlein:Patrys Ltd: Consultancy. Dubljevic:Patrys Ltd: Employment. Einsele:Celgene GmbH: Consultancy, Honoraria, Research Funding. Topp:Patrys Ltd: Honoraria.